Lice and mite infestations of cattle in Iceland - Matthías Eydal 1952-; Sigurður H. Richter 1943- (2010)
The aim of the present study was to survey lice and mite species infesting cattle in Iceland and to evaluate their prevalence on farms, prevalence and site preferences on the animals and correlation with dermatological symptoms. The survey included two separate investigations, a combing study including 50 calves and 50 dairy cows, and a study of skin samples including 27 bullocks and 28 dairy cows. The animals came from farms in Southwest Iceland. In the combing study five preselected areas on each animal were combed. Two lice species were found, the chewing louse Bovicola bovis and the sucking louse Solenopotes capillatus. Lice were found at 7 of 10 farms. B. bovis was found at 50% and S. capillatus at 40% of the farms and both species occurred at 20% of the farms. Lice were found on 40% of the calves and 4% of the cows. B. bovis was found on 28% of the calves and 2% of the cows. S. capillatus was detected on 16% of the calves and 2% of the cows. B. bovis was most prevalent on back and rump, less prevalent on the head, neck and tail and was not detected on the front leg. S. capillatus was most prevalent on the neck, then head and front leg, and was least prevalent on the posterior back and rump and on the tail. Minor dermatological signs were seen on two cows and three calves. In the study of skin samples, samples were taken from five preselected sites of the animals. In this study the hair follicle mite Demodex bovis was found in the skin of the neck of one bullock (1.8%). No macroscopic skin disorders were observed on the samples. Markmið rannsóknarinnar var að athuga hvaða ytri sníkjudýr finnast á íslenskum nautgripum, kanna tíðni þeirra á búum, sýkingartíðni og staðsetningu á gripunum og tengsl við sjúkdómseinkenni. Rannsóknin skiptist í kembirannsókn (50 kálfar og 50 mjólkurkýr) og húðsýnarannsókn (27 geldneyti og 28 mjólkurkýr). Bú voru valin af handahófi á Suðvesturlandi. Í kembirannsókninni voru fimm fyrirfram ákveðin svæði á hverjum grip kembd. Tvær lúsategundir fundust, naglúsin Bovicola bovis og ...